Analysis of strategies in soccer as a function of European and domestic competition - James, N.; Mellalieu, S. D.; Hollely, C. (International Journal of Performance Analysis in Sport, 2002)
Existing investigations of strategies in soccer using notational analysis have traditionally focused upon nomothetic analysis of international competitions such as World or European Championships (i.e., Luhtanen et al., 2001; Yamanaka, et al., 2001). To enhance the applied benefit of notational analysis idiographic assessment of teams, strategies are required to establish meaningful normative profiles (Hughes et al., 2001). A need also exists to examine individual player behaviours to determine potential influences upon team strategies. The aim of the current study was to assess the strategies of a team in both domestic and European competition over a competitive season. Matches of a British professional soccer team were analysed using a computerised behavioural measurement package with regard to frequency and duration of possession in designated areas of the soccer field. European matches were characterised by more play in pre-defensive areas at the expense of pre-offensive areas compared to domestic matches. Attacking play was found to occur more frequently down the right hand side of the pitch in domestic compared to Europe. Variability was also observed between ball possession and passing difficulty made by individual players in each pitch area. The findings suggest that differences in tactical strategies are evident at both individual and team levels as a function of the nature of the competition. Individual roles therefore appear to be dictated by playing position, team tactics and game circumstances.